2020
DOI: 10.1016/j.vas.2020.100115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a slatted floor on bacteria and physical parameters in litter in broiler houses

Abstract: In this study, a new housing system for broiler was tested. This system consisted of a slatted floor area and a littered area with the aim of improving litter quality. Two experimental broiler houses were provided. In house 1, a slatted floor was installed below the drinker and feedlines. Littered areas flanked the slatted floor. Broiler house 2 reflected conditions in commercial systems, consisting of a full littered area. Litter samples were taken at day 11 and at day 32 of the fattening period. Manure sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
0
12
0
2
Order By: Relevance
“…(2020) ; Boggia et al. (2019) ; Heitmann et al. (2020) Water activity—water movement in the litter Eriksson De Rezende, Mallinson et al.…”
Section: Resultsmentioning
confidence: 99%
“…(2020) ; Boggia et al. (2019) ; Heitmann et al. (2020) Water activity—water movement in the litter Eriksson De Rezende, Mallinson et al.…”
Section: Resultsmentioning
confidence: 99%
“…A multifactorial evaluation of an innovative flooring system in broiler production is important to ensure the compatibility of animal welfare and the environment. Previous studies have shown positive effects of a partially perforated flooring system on animal-based welfare indicators, without affecting production performance or the occurrence of bacteria [ 12 , 13 ]. Positive effects of elevated perforated areas on health- and behavior-based welfare indicators are confirmed by numerous studies [ 18 , 19 , 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the litter provides a potential reservoir for antibiotic-resistant bacteria [ 9 ] that can be transmitted to humans via the food chain [ 10 , 11 ]. Two studies were carried out in the past comparing an innovative partially (50%) perforated flooring system with a littered flooring system [ 12 , 13 ]. One feature of the partially perforated flooring system is an elevated perforated area in the section of feed and water supply, accessible by perforated ramps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach is the use of slatted flooring. Recent studies evaluated the relationship between slatted flooring and the level of Escherichia ( E. ) coli , coliform, and antimicrobial resistant E. coli [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%